The Advantages and Challenges of Digital Resources as Supporting Learning Media in Teaching Narrative Writing Text - Rani Santika; Rafi Farizki; Ahmad Jamal; Irfan Azis (Eduvest - Journal of Universal Studies, 2024)
This research aims to investigate the advantages and challenges of digital resources as supporting learning media in teaching narrative writing text. This research used qualitative methods by using descriptive qualitative design. The data was obtained through document analysis, observation and interview. The subject of this research were two English teachers in Vocational High School Ibnu Khaldun at 10th Grade the academic years of 2022/2023 who implemented digital resources in teaching narrative writing text. The findings of this research show there are four advantages of digital resources. First, digital resources help English teachers in delivering material. Second, access a wider range of material and resources. Third, it can create fun and enjoyable classes. Fourth, improve the quality of learning by new activities. Furthermore, there are three challenges, First, limited internet connectivity. Second, choosing digital resources appropriately. Third, the lack of digital resources implemented by English teachers.